Persepsi Terhadap Diri dan Lingkungan Pada Remaja Penyalahguna Napza (Narkotika, Psikotrpoika dan Zat Adiktif) - Tina Afiatin (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2001)
The purpose of this research is to know the perception to the characteristic of themselves and the environment on adolescents abuser of narcotic, psy chotropic and addictive substance. The characteristic of themselves includes physical condition aspect, psychological, social and religious fife. Whtie the environment mean the family, the school and the society around subjects.Carrying out a depth interview and observation to 10 (ten) adolescents abuser of narcotic, psychotropic and addictive substance (7 males, 3 females) collected the data. They ltved in Sleman. Yogyakarla territory. Besides that also the information about the subjects life were Inquired to 10 (ten) informants who knew about the subjects life.The result of data analysis qualitatively showed that the subjects perception to themselves generally (80%) felt not satisfied enough with their physice/ condition. Psychologically. they had lack of self-confidence, they felt inferior in the social mteraction and they felt less of religious life experience. Their per ception to the fam/fy, they felt that they were not quite accepted, they were not quite understood and they often felt be neglected. They were also not close with their father particularly. Perception to the school environment, generally (70%) they felt were accepted and popular although they realized also that their popularity in negative cases. Most subjects (90%) were not active and in volved in the school activities. Perception to the society environments gener ally (80%) they felt they could be accepted, even they felt closer compared with ,n school environment. The social activities in their area more empha sized physical development aspects, they had less of interest on education aspect and guiding of religious life.The result of information from informants generally (90%) they stated thatmost subjects (80%) were spoiled by their parent with material. they got lack of attention and they were usually egoists. They commonly was easy to be per suaded by their friends to follow negative deeds. such as sitting idly on the street and disturbed other people, drinking alcoholic drink and drug abuse. Nevenheless, actually some subjects (8) also had helpful character in the social activities. Kata Kuncl: Persepsi, Remaja, NAPZA